Seasonal Adaptation in Feed Management: Assessing Forage and Feedstuff Variations in Small-Sized Dairy Farms in Boyolali, Central Java - Kumalasari, Nur Rochmah; Suharti, Sri; Zahra, Windi Al; Rosmalia, Annisa; Permana, Idat Galih; Sunardi, Sunardi (Jurnal Sain Peternakan Indonesia, 2025)
Small dairy farms in tropical regions frequently encounter feed shortages and quality fluctuations between seasons, which can substantially affect milk production. This research aimed to evaluate the ability of small-scale dairy farms to adapt to and manage feed fluctuations in response to seasonal changes.  The research employed an exploratory design, with samples collected using nested sampling methods. Three samples were collected according to the season, specifically during the dry season (August 2024) and the rainy season (January 2025), from the Cepogo and Selo Subdistricts in Boyolali.  Feed samples collection was conducted in five stages: 1) desk study of the research area; 2) field visiting; 3) feed samples; 4) forage samples collection; and 5) feed analysis using proximate analysis (AOAC, 2005).  The results showed differences in feeding management among farmers related to their dairy animal structures.  The highest dry matter content in the forage was found in rice straw (60.4% DM), which dominated dry season use, while the highest crude protein content was observed in calliandra (23.5%) among the forages. Five coproducts have high dry matter content with varying crude protein and crude fibre levels.  The research concluded that small-sized dairy farms can adapt and manage feed fluctuations based on seasonal changes by making forage and concentrate choices available.